Can small reservoirs enhance sustainable agricultural development in Sub-Saharan Africa?: broadening the analytical horizons - Venot, Jean-Philippe; Hirvonen, M. (2010)
Small reservoirs punctuate the landscapes of rural sub-Saharan (West) Africa. It has become an established development truth that such water infrastructures offer benefits in terms of food production and poverty alleviation -this despite the fact that performance and adoption study show, at best, patchy records. This paper uses the notion of boundary object to understand this apparent contradiction. It argues, firstly, that small reservoirs can be cast in a variety of ways that speak to various communities of practice; they intersect multiple narratives and fulfil a plurality of interests. This explains their omnipresence. Secondly, small reservoir projects embed assumptions of societies as closed systems that can be altered to predefined ends by technological means and institutional reforms. These assumptions also inform the monitoring and evaluation procedures of small reservoirs. The latter assess the outcomes and impacts of small reservoirs against techno-economic visions of development, and in so doing, identify the 'failure' of small reservoirs due to economic and institutional shortcomings. We argue that local communities do make use of small reservoirs, but seldom in the ways implied by policy discourse and development strategies. Small reservoirs, we argue, induce new and multiple claims and uses of natural resources, new meanings of space and relationships to environments. As such, they do act as motors of social change, but in considerably more complex ways than is conventionally claimed. Alternative explanatory frameworks are needed to better comprehend the value they bestow for multiple actors in order to design more responsive and flexible policies for sustainable agricultural development.